Roman Analysis of Tenggelamnya Kapal Van Der Wijck by Hamka through Critical Literature Approach - Ahmad Ridhai Asis; Burhanuddin (Sekolah Tinggi Agama Islam Negeri Majene, 2022)
This study aims to describe the results of the analysis of the Roman Tenggelamnya Kapal Van Der Wijck by Hamka. This research approach used a critical literacy approach to criticize the meaning or purpose of the author expressing his message through a symbolic romance. The results of this study indicated that : (1) Hamka presented events through the theme of an unsuccessful love story/unacceptable love story which critically symbolized the desire for independence of the natives of colonialism that had not been conveyed ; (2) The plot used combines the loose groove and the back-and-forth groove which critically symbolizes a long and winding to struggle ; (3) The point of view used was third person singular which was a feature of the author's symbolic expression that criticized government associability ; (4) The characters of the novel created by the author symbolized by the indigenous context at that time critically symbolizing fighters and allies as well as invaders that were always in conflict ; (5) The message conveyed was a moral message that focused on the character of Zainuddin who struggled on differences of ethnicity, customs, and ideology which critically symbolized the struggle which in context at that time was not yet fully independent from colonialism